Transduction with Integration-Defective Mutants of Salmonella typhimurium Bacteriophage KB1 - McIntire, Sarah A. (1974)
Phage KB1 has gained use as a generalized transducing phage for Salmonella typhimurium, including strains resistant to phage P22. Integration-defective mutants of KB1 have now been isolated; one of these, int-1, is recommended for transduction when nonlysogenic recombinants are desired.